Primary Care Physicians' Personal and Professional Attributes Associated With Forgoing Own Care and Presenteeism: A Cross Sectional Study - Christine Cohidon; Liv Mahler; Barbara Broers; Thierry Favrod-Coune; Amir Moussa; Paul Sebo (Frontiers Media S.A., 2022)
Objective: The aim of this study was to describe the prevalence of forgoing care and forgoing sick leave among primary care physicians (PCPs) in Switzerland and to investigate associated factors.Methods: A random sample of 1,000 PCPs in French-speaking regions of Switzerland (participation rate: 50%) was asked whether they had forgone care and sick leave during the last year. Sociodemographic, personal and occupational characteristics were recorded. Logistic regressions were performed to study these behaviours.Results: 37% of respondents reported at least one episode of forgoing care and 29% reported an episode of forgoing sick leave. No associations were found between individual characteristics and forgoing care. A heavy workload was the most common reason evoked for forgoing care. Coming to work when sick (presenteeism) was associated with female sex, younger age, having a chronic illness, working in a suburban area and working full-time.Conclusion: A high proportion of PCPs in Switzerland is forgoing own care and continues to work despite sickness. New generations of PCPs should require careful monitoring, and specific solutions should be sought to reduce these harmful behaviours.